2015
DOI: 10.1002/jms.3626
|View full text |Cite
|
Sign up to set email alerts
|

Combining a NHS ester and glutaraldehyde improves crosslinking prior to MALDI MS analysis of intact protein complexes

Abstract: Protein complexes play pivotal roles in cellular life. Nevertheless, their characterization remains a substantial challenge. Mass spectrometry (MS) is an emerging tool to study protein assemblies, and electrospray ionization (ESI) is often used because it preserves non-covalent interactions. Matrix-assisted laser desorption/ionization (MALDI) represents an important alternative to ESI because it is more tolerant to salts and detergents (e.g. necessary in the case of membrane complex analyses). Prior to MALDI-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, restricting by experimental cost, the concentrations of aa-RNA was just increased to 0.3 mM, higher concentration of aa-RNA are suggested for users in future studies, which may further enhance the reaction efficiency and reduce the cost. Unlike most of protocols for DNA or protein labeling [ 24 , 27 , 28 ], this work demonstrated that the optimal concentration of DMSO is 45–55% (vol/vol). Suggesting that sufficient DMSO was required to achieve efficient labeling of aa-RNA, and the concentration of DMSO should be kept at 45–55% (vol/vol) while avoiding high (>70%) or low (<30%) concentration of DMSO.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, restricting by experimental cost, the concentrations of aa-RNA was just increased to 0.3 mM, higher concentration of aa-RNA are suggested for users in future studies, which may further enhance the reaction efficiency and reduce the cost. Unlike most of protocols for DNA or protein labeling [ 24 , 27 , 28 ], this work demonstrated that the optimal concentration of DMSO is 45–55% (vol/vol). Suggesting that sufficient DMSO was required to achieve efficient labeling of aa-RNA, and the concentration of DMSO should be kept at 45–55% (vol/vol) while avoiding high (>70%) or low (<30%) concentration of DMSO.…”
Section: Discussionmentioning
confidence: 74%
“…However, restricting by experimental cost, the concentrations of aa-RNA was just increased to 0.3 mM, higher concentration of aa-RNA are suggested for users in future studies, which may further enhance the reaction efficiency and reduce the cost. Unlike most of protocols for DNA or protein labeling [24,27,28], this work demonstrated that the optimal concentration of DMSO is 45-55% (vol/vol).…”
Section: Discussionmentioning
confidence: 76%
“…In current protocols, it is strongly recommended to remove this chemical before the reaction with NHS esters, since it involves a primary amino functional group and is usually present in the 100 mM concentration range. Moreover, TRIS has been proposed as a reagent to block excess NHS esters. , …”
mentioning
confidence: 99%
“…Moreover, TRIS has been proposed as a reagent to block excess NHS esters. 1,8 Here, we inadvertently biotinylated a nanobody which is specific for green-fluorescent protein (GFP) 9 between a nanobody biotinylated in the presence or absence of 100 mM TRIS (Figure 1). Based on these results, we hypothesized that the pH might have an impact on the biotinylation reaction and that a higher or lower pH might lead to a preferred reaction with the amino groups of the antibody compared to the function in TRIS.…”
mentioning
confidence: 99%